Prevalence of Expanded Dengue Syndrome in Patients with Dengue Virus Infection at the Dr. Soetomo Hospital Surabaya in 2017 – 2018 - Avina Fimas Adissadah; Aryati Aryati; Suhintam Pusarawati (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2020)
Dengue Fever (DF) or Dengue Hemorrhagic Fever (DHF) is one of the infectious diseases that attracts much global attention, especially Indonesia because it impacts the mortality rate of the people in the world if adequate treatment is not given. Expanded Dengue Syndrome (EDS) is a clinical manifestation involving several organs such as lungs, liver, kidney, heart, and brain-related to dengue infections, with or without plasma leakage. This study aimed to determine the prevalence of expanded dengue syndrome in patients with dengue virus infection at the Dr. Soetomo Hospital in 2017–2018. Based on its purpose, the sampling technique used in this study was the total sampling of patients with DVI who admitted to Dr. Soetomo Hospital Surabaya. Every pediatric and adult patient who met the criteria were included in this study until a certain period in 2017–2018.  After the data collection, only thirty samples of EDS from the 196 sample data were collected. Thirty patients with expanded dengue syndrome had a manifestation of different organs. Such as: neurological, cardiac, respiratory system, gastro-hepatic, and kidneys. The laboratory test results showed that most platelet counts of 51,000 – 100,000 were found in seventeen patients, while the range of hemoglobin and hematocrit was normal. From a total of thirty samples of dengue virus infection patients with EDS, there were only eighteen patients who did a serological test. The most found serological results were (+/-) anti-dengue IgM and (+) anti-dengue IgG (40%).